2017
DOI: 10.1016/j.ecoenv.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Reprint of: CYP1A protein expression and catalytic activity in double-crested cormorants experimentally exposed to Deepwater Horizon Mississippi Canyon 252 oil

Abstract: Double-crested cormorants (Phalacrocorax auritus, DCCO) were orally exposed to Deepwater Horizon Mississippi Canyon 252 (DWH) oil to investigate oil-induced toxicological impacts. Livers were collected for multiple analyses including cytochrome P4501A (CYP1A) enzymatic activity and protein expression. CYP1A enzymatic activity was measured by alkoxyresorufin O-dealkylase (AROD) assays. Activities specific to the O-dealkylation of four resorufin ethers are reported: benzyloxyresorufin O-debenzylase (BROD), ethox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Orally dosed birds received 5.2 ± 0.3 ml oil/kg BW and 8.4 + 0.9 ml oil/kg BW per day totaling 208 and 235 ml respectively, while the externally dosed birds likely only consumed (based on Hartung, 1963) a total of 38-38.5 g over 21 days , or approximately 0.9 ml/kg BW daily. There were additional signs and symptoms of this toxicity reported in other manuscripts describing these studies (Alexander et al, 2017;Cunningham et al, 2017;Harr et a, 2017a, c, d;Pritsos et al, 2017). These include increases in relative organ weight, hypertrophy and histopathological changes at necropsy, development of hemolytic anemia, inflammation and atrophy (Harr et al, 2017a(Harr et al, , 2017c, as well as newly documented clotting dysfunction, cardiomyopathy and associated functional losses (Harr et al, 2017d).…”
Section: Discussionmentioning
confidence: 95%
“…Orally dosed birds received 5.2 ± 0.3 ml oil/kg BW and 8.4 + 0.9 ml oil/kg BW per day totaling 208 and 235 ml respectively, while the externally dosed birds likely only consumed (based on Hartung, 1963) a total of 38-38.5 g over 21 days , or approximately 0.9 ml/kg BW daily. There were additional signs and symptoms of this toxicity reported in other manuscripts describing these studies (Alexander et al, 2017;Cunningham et al, 2017;Harr et a, 2017a, c, d;Pritsos et al, 2017). These include increases in relative organ weight, hypertrophy and histopathological changes at necropsy, development of hemolytic anemia, inflammation and atrophy (Harr et al, 2017a(Harr et al, , 2017c, as well as newly documented clotting dysfunction, cardiomyopathy and associated functional losses (Harr et al, 2017d).…”
Section: Discussionmentioning
confidence: 95%
“…Polycyclic aromatic hydrocarbons are known to bind to and activate the AhR, and the xenobioticmetabolizing monooxygenases, cytochrome P450 (CYP) 1A and 1B, bioactivate PAHs to more toxic metabolites after AhR activation (Schimada and Fujii-Kuiyama 2004). Activation of the PAH-responsive AhR pathway and a phase I response have been previously documented in other species of oil-exposed birds (e.g., Seaside Sparrow [Ammospiza maritima], Perez-Umphrey et al 2018; Bonisoli-Alquati et al 2020; double-crested cormorant, Alexander et al 2017). In addition, CYP1A activity is frequently measured as EROD induction, a common biomarker for PAH exposure in birds (Head et al 2015), and Bianchini and Morrissey (2018) reported elevated EROD activity in the high-dose group relative to controls in these same birds.…”
Section: Ahr Activationmentioning
confidence: 98%
“…Short of proving lethal, however, external (dermal) oil-contamination and respiratory exposures in birds induces increased lung-epithelial CYP1A expression, skin irritation, conjunctivitis and corneal ulcers, and also reduces the feathers' capacity to repel water, which leads to increased heat loss, and reductions in insulating capacities, buoyancy, and flight performance (Leighton, 1993;Jenssen, 1994;O'Hara and Morandin, 2010;Munilla et al, 2011;Fiorello et al, 2016;Maggini et al, 2017b;Dubansky et al, 2018). Beyond these effects of dermal and respiratory oil exposures, after an oil spill many birds continue being orally exposed for months and even for decades to varying concentrations of petroleum leading also for sublethal effects (Alexander et al, 2017;Esler et al, 2018). Oral exposure to oil occurs via ingestion of contaminated prey, grit and water during foraging, and also occurs during attempts for cleaning (preening) of oilcontaminated feathers (Hartung and Hunt, 1966;Pritsos et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%